Propranolol decreases retention of fear memory by modulating the stability of surface glutamate receptor GluA1 subunits in the lateral amygdala. (23rd October 2015) - Zhou, Jun; Luo, Yi; Zhang, Jie‐Ting; Li, Ming‐Xing; Wang, Can‐Ming; Guan, Xin‐Lei; Wu, Peng‐Fei; Hu, Zhuang‐Li; Jin, You; Ni, Lan; Wang, Fang; Chen, Jian‐Guo
Abstract : Background and Purpose: Posttraumatic stress disorder (PTSD) is a mental disorder with enhanced retention of fear memory and has profound impact on quality of life for millions of people worldwide. The β‐adrenoceptor antagonist propranolol has been used in preclinical and clinical studies for the treatment of PTSD, but the mechanisms underlying its potential efficacy on fear memory retention remain to be elucidated. Experimental Approach: We investigated the action of propranolol on the retention of conditioned fear memory, the surface expression of glutamate receptor GluA1 subunits of AMPA receptors and synaptic adaptation in the lateral amygdala (LA) of rats. Key Results: Propranolol attenuated reactivation‐induced strengthening of fear retention while reducing enhanced surface expression of GluA1 subunits and restoring the impaired long‐term depression in LA. These effects of propranolol were mediated by antagonizing reactivation‐induced enhancement of adrenergic signalling, which activates PKA and calcium/calmodulin‐dependent protein kinase II and then regulates the trafficking of AMPA receptors via phosphorylation of GluA1 subunits at the C‐terminus. Both i.p. injection and intra‐amygdala infusion of propranolol attenuated reactivation‐induced enhancement of fear retention. Conclusions and Implications: Reactivation strengthens fear retention by increasing the level of noradrenaline and promotes the surface expression of GluA1 subunits and the excitatory synaptic transmission in LA. These findings uncover one mechanism underlying the efficiency of propranolol on retention of fear memories and suggest that β‐adrenoceptor antagonists, which act centrally, may be more suitable for the treatment of PTSD.